Il corpo come spazio espressivo. La figura del templum divinatorio in Merleau-Ponty - Dalmasso, Anna Caterina (Scenari, 2024)
The term “to contemplate” originates from the divinatory practice of ornithomancy, the augural observation of the flight of birds, which, alongside the rite of hepatoscopy, the interpretation of the entrails of sacrificial animals, played an important role in Etruscan-Latin ritual practices. The divinatory observation was preceded by the delimitation of a boundary, called templum, within which the signs would assume the meaning of divine omens. Con-templating then is nothing other than the gesture of looking within the boundaries of the templum. This divinatory device is evoked in some passages of Merleau-Ponty’s work in order to illuminate the lived body as an eminently expressive space, which bestows meanings that transcend its objective space, and as a virtual contour that mediates interobjective and intersubjective relations, outlining a topological dimension.